2011
DOI: 10.1136/hrt.2010.218677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contrast-induced acute kidney injury with transient or persistent renal dysfunction on long-term outcomes of patients with acute myocardial infarction undergoing percutaneous coronary intervention

Abstract: Objective To investigate the long-term prognostic implications of contrast-induced acute kidney injury (CI-AKI) with transient or persistent renal dysfunction in acute myocardial infarction (AMI) patients undergoing percutaneous coronary intervention (PCI). Design A retrospective observational registry study. Setting Clinical follow-up after PCI. Patients and methods A total of 1041 PCI-treated AMI patients from the Infarction Prognosis Study registry. CI-AKI was defined as an increase in serum creatinine (>25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 22 publications
7
147
2
3
Order By: Relevance
“…In addition to contrast-induced nephropathy, 4,5 links between renal dysfunction and oxidative stress, inflammation, altered cytokine levels, platelet activation, and hypercoagulable or thromboresistant state have been confirmed, and these data on the course of AKI (whether AKI resolved or persisted) and the need for hemodialysis or renal replacement therapy during or after the index hospitalization, which have significant prognostic implications. 8 Fourth, the sample size for stratified analysis in Killip class 4 might have been too small to show an association between AKI and in-hospital mortality, although there was a marginally significant association on multivariate analysis. Finally, the volume of contrast agent used during coronary angiography and PCI was not available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to contrast-induced nephropathy, 4,5 links between renal dysfunction and oxidative stress, inflammation, altered cytokine levels, platelet activation, and hypercoagulable or thromboresistant state have been confirmed, and these data on the course of AKI (whether AKI resolved or persisted) and the need for hemodialysis or renal replacement therapy during or after the index hospitalization, which have significant prognostic implications. 8 Fourth, the sample size for stratified analysis in Killip class 4 might have been too small to show an association between AKI and in-hospital mortality, although there was a marginally significant association on multivariate analysis. Finally, the volume of contrast agent used during coronary angiography and PCI was not available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study 16) stated that CIN was significantly correlated with long-term mortality in the entire cohort and in patients with chronic kidney disease (CKD) but not in patients without CKD. A study 17) on AMI patients undergoing PCI showed that patients with transient renal dysfunction had a lower two-year event rate of death or dialysis compared with those with persistent renal dysfunction, but a higher event rate compared with those without CIN. Farhan, et al 18) revealed that advanced deterioration in renal function after PCI is an independent predictor for in-hospital and long-term mortality rates.…”
Section: )mentioning
confidence: 99%
“…[1][2][3] Although AKI is generally a reversible condition, patients developing this complication post PCI may experience up to 20-fold increase in their in-hospital mortality risk. 4 Interpretation of results reported by previous studies on the association between AKI and mortality post PCI is hampered by the fact that both outcomes share common risk factors, such as hemodynamic instability, heart failure, diabetes mellitus, and preexisting chronic kidney disease.…”
mentioning
confidence: 99%